Antibacterial Resistance in Lower Respiratory Tract Bacterial Pathogens: A Multicenter Analysis from Turkey - Aylin Uskudar Guclu; Aylin Altay Kocak; Mehtap Akcil Ok; Bulent Tutluoglu; Ahmet Celal Basustaoglu; Respiratory Study Group (Journal of Infection in Developing Countries)
Introduction: This study aimed to evaluate the etiology of lower respiratory tract infections (LRTIs) and their antibiotic resistance.